From Specialised Classrooms to Mainstream Classrooms: A Study on the Inclusion of Students with Special Educational Needs from the Voices of Their Mainstream Peers - Carmen María Caballero (MDPI AG, 2024)
The modalities of schooling and the educational measures for students with special educational needs (SENs) are postulated as important aspects within the field of study of inclusive education. The general objective of this research is to analyse the processes, through the voice of their peers, for the inclusion of students with SENs enrolled in specialised classrooms (SCs) in mainstream centres in Spain when they attend mainstream classrooms (MCs). The design of the research is mixed (QUAN-Qual), non-experimental, and descriptive. The participants in the quantitative phase were 2649 peers from MCs that have students enrolled in the SCs, and the participants in the qualitative phase were 57 students from MCs. A questionnaire designed ad hoc was used for collecting the quantitative information and discussion groups for the qualitative information. This study shows the barriers and facilitators towards the inclusion of students in the SU within mainstream centres or classrooms. Among the facilitators which stand out is the wish of classmates from mainstream classrooms to share times, spaces, and activities with their classmates with SENs from the SU. Among the barriers highlighted by a large number of students in the MCs are the fact that they do not participate in group activities with their peers with SENs and that the latter do not usually participate in common activities developed at the centre (like celebrations or excursions).